2012
DOI: 10.1063/1.4736614
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of the low-temperature cluster-glass magnetic state of Nd2/3Ca1/3MnO3 perovskite

Abstract: In the presented study we have revealed a giant exchange bias in a colossal magnetoresistance Nd 2/3 Ca 1/3 MnO 3 perovskite at low temperatures, evident of an intrinsic exchange coupling in this compound. The phenomena found confirms our previous assumption that the low-temperature magnetic structure of the compound is represented by small (nanosized) ferromagnetic clusters immersed within the charge-ordered antiferromagnetic matrix. Magnetic behavior of the Nd 2/3 Ca 1/3 MnO 3 perovskite is consistent with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…2,[5][6][7] In the materials which are single-phase at high temperatures but exhibit spontaneous phase separation at low temperatures due to first-order phase transitions, the exchange bias phenomenon has been found relatively recently. Among these compounds, perovskite manganites [8][9][10][11][12][13] and cobaltites [14][15][16][17] should be mentioned. For instance, it was shown that the compound Pr 2/3 Ca 1/3 MnO 3 with spontaneous phase separation consists of an antiferromagnetic matrix with embedded ferromagnetic clusters.…”
Section: Introductionmentioning
confidence: 99%
“…2,[5][6][7] In the materials which are single-phase at high temperatures but exhibit spontaneous phase separation at low temperatures due to first-order phase transitions, the exchange bias phenomenon has been found relatively recently. Among these compounds, perovskite manganites [8][9][10][11][12][13] and cobaltites [14][15][16][17] should be mentioned. For instance, it was shown that the compound Pr 2/3 Ca 1/3 MnO 3 with spontaneous phase separation consists of an antiferromagnetic matrix with embedded ferromagnetic clusters.…”
Section: Introductionmentioning
confidence: 99%